The Effect of Physical Activity on Level of Anger among Individuals with Autism - Mehmet Ilkım; Halil Tanır; Mehmet Özdemir; İbrahim Bozkurt (Türk Spor ve Egzersiz Dergisi)
This study was undertaken to investigate the effect of physical activity on anger level in autistic individuals. Study sample included parents of 40 autistic children (n=20 experimental and n=20 control) aged 10-14 years from Malatya Private Sevgi Yolu Rehabilitation Center. Three days a week for 16 weeks, the experimental group did the activities of one-hour walk, jogging, double-leg jump, and walking along a balancing beam. Individuals in the control group continued their daily routine without participating in any activity during this period. Anger levels of autistic individuals were identified using the Trait Anger and Anger Expression Inventory (TAAEI) developed by Spielberger et al. (1983) and adapted to Turkish by Özer (1994). The inventory was completed by the parents of the individuals both in the experimental and control groups following the 16-week activity program. The collected data was analyzed at the significance level of 0.05 (i.e. a confidence level of 95%) in SPSS version 22.0. Statistical analysis indicated significant differences between trait anger, controlled anger, expressed anger and suppressed anger scores (p lt;0.05). The results showed that anger levels of the autistic individuals participating in the physical activity program were lower and the physical activity in autistic individuals helped anger control. It is recommended that autistic individuals participate in low intensity activities for at least 3 days a week. By teaching autistic individuals how to keep their anger under control, interpersonal and family conflicts, feelings of guilt, low self-esteem and some behavioral (e.g. shyness, crying, unhappiness, anorexia, bulimia) and physiological problems (e.g. sweating, headache, difficulty in breathing) can be avoided.